Increasing attractiveness and image recognition of Bulgaria as a tourism destination - Preslav Mihaylov Dimitrov; Mariya Zlatkova Stankova; Ivanka Vasenska; Dimitria Uzunova (Tourism & Management Studies)
The concept of tourism destination attractiveness does not constitute a new topic in the scientific literature in the field of tourism. On the contrary, attention has been brought towards it since last century’s 60 years. For a relatively long period, however, the existing studies show out that they not only did not lead to the creation of a single platform for evaluation, but rather have resulted in a fragmentation of the researchers’ opinions. At present, numerous authors have been trying to identify the destination’s attractiveness and factors influencing tourists’ decision-making process to assess a given area as a desirable vacation spot. The attractiveness of the area does not only depend on the characteristics of its corresponding site and the local population, but also from tourist cognitive image perception of the destination. The present paper comprises the results from two separate studies conducted in parallel from 2011 to 2014 and it aims to outline the various factors that could influence the process of increasing of attractiveness and image recognition of Bulgaria as a tourism destination. For this purpose, a multifactorial analysis of the whole tourism destination of Bulgaria was applied alongside with a cultural profiling of an almost iconic and landmark micro destination for cultural tourism such as the town of Plovdiv (or the ancient Phillipopolis found by the king Phillip the Second, the father of Alexander the Great).